HCV knowledge, disclosure practices, and risk perceptions among gay and bisexual men who do and do not engage in group sex while using drugs. Issue 10 (2nd October 2020) - Brener, Loren; Murphy, Dean A.; Cama, Elena; Murray, Joel; Fraser, Neil; Ellard, Jeanne
ABSTRACT : Research suggests that hepatitis C virus (HCV) transmission is more likely among gay and bisexual men (GBM) who engage in sexually adventurous practices, including group sex while using drugs. The current study explored drug use, sexual practices, HCV knowledge, HCV disclosure, and beliefs about HCV transmission among GBM ( n = 193) reporting group sex after/while using drugs compared to those who did not. Survey findings indicate that men who participated in group sex while using drugs were more likely to have engaged in other sexually adventurous practices, ever injected drugs, have greater knowledge of HCV, and to be living with HIV. They were also more likely to perceive themselves at risk of acquiring HCV and to know that their sexual activities put them at risk. Interestingly, they had lower expectations of HCV disclosure and were less concerned about the HCV status of their partners. The lower expectations around disclosure and concern about the HCV status of their partners reflect the challenges for GBM in managing HCV transmission where there are limited effective behavioural strategies for reducing sexual transmission, This research also highlights the need to promote HCV testing and treatment to GBM who engage in group sex while using drugs.